IMPLEMENTASI ETIKA BERDAGANG DENGAN SIFAT SIDDIQ, TABLIGH, AMANAH, FATHANAH PADA WAROENG STEAK AND SHAKE CABANG BOULEVARD MAKASSAR - Trisnawati, Eva; Wahab, Abdul; Habbe, Hamid (Economos : Jurnal Ekonomi dan Bisnis, 2021)
Ethics in Islamic business aims to teach people to cooperate, work hand in hand, and distance themselves from jealousy and envy and things that are not following syariah. Business ethics in Islam also functions as a regulator of the economic activities of traders. Each individual who carries out economic activities, whether a businessman or who carries out economic activities, must know Islamic business ethics to avoid actions that are prohibited by Allah SWT. The research method used is qualitative research with the type of case study research that used to examine an activity with direct observation techniques at waroeng steak and shake of boulevard Makassar branch with business ethics that use the basic characteristics possessed by the Prophet in trading, namely siddiq, tabligh , Amanah, fathanah. The results of the study indicated that the four basic characteristics of Islamic trading have been implemented in waroeng steak and shakes at the Boulevard Makassar branch.